Helminth Parasites of Three Anuran Species during Reproduction and Drought in the Brazilian Semiarid Caatinga Region - Madelaire, Carla Bonetti; Franceschini, Lidiane [UNESP]; Morais, Drausio Honorio; Gomes, Fernando Ribeiro; Da Silva, Reinaldo José [UNESP] (American Society of Parasitologists, 2020)
We investigated the mean abundance of helminths and analyzed helminth composition and structure at the infracommunity and component community levels for 3 anuran species (Pleurodema diplolister, Rhinella jimi, and Rhinella granulosa) from the Caatingas, a semiarid Brazilian region characterized by accentuated seasonality and unpredictability of rains. Data were collected during the reproductive period and during drought, when P. diplolister estivated buried underground but R. jimi and R. granulosa remained foraging actively. We expected higher parasitological parameters during the reproductive period when compared to drought for these 3 anurans. We also expected higher parasite infection in the Rhinella species and higher similarity between their helminth parasite communities when compared to the estivating species, P. diplolister. Contrary to our hypothesis, the season was not related to parasite community structure. As predicted, the Rhinella toads shared more similar species composition of parasite communities. These similarities in the composition of the parasite community between Rhinella species could be due to similar temporal/spatial patterns of activity and phylogenetic proximity. Pleurodema diplolister hosted a more restricted helminth fauna, a result that might be associated with estivation restricting the temporal window available to acquire parasites. This study also presents new helminth fauna records for R. jimi and P. diplolister, and the first helminth fauna record of R. granulosa from the Caatingas in semiarid Brazil.
Keywords: Community; Estivation; Parasite Component; Parasite Infracommunity; Seasonality; Toad